2015
DOI: 10.1021/jacs.5b08744
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Intermediates Kinetics in Solution Investigated by Electrospray Ionization Mass Spectrometry: Diaurated Complexes

Abstract: A new method to investigate the reaction kinetics of intermediates in solution by electrospray ionization mass spectrometry is presented. The method, referred to as delayed reactant labeling, allows investigation of a reaction mixture containing isotopically labeled and unlabeled reactants with different reaction times. It is shown that we can extract rate constants for the degradation of reaction intermediates and investigate the effects of various reaction conditions on their half-life. This method directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…In our experiment, when formic acid was added to the reaction mixture containing 4 mm Ph 3 PAuNTf 2 and 200 mm propargyl acetate alkyne 1 to adjust the solution pH to 4.5, the reaction occurred and ions of m/z =193 and 1109 were all observed (Figure 7S in the Supporting Information), thereby excluding the possibility of involvement of L-Au-OH species in the reaction. Such an acid effect was also noted in the recent report by Roithova et al [17] …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In our experiment, when formic acid was added to the reaction mixture containing 4 mm Ph 3 PAuNTf 2 and 200 mm propargyl acetate alkyne 1 to adjust the solution pH to 4.5, the reaction occurred and ions of m/z =193 and 1109 were all observed (Figure 7S in the Supporting Information), thereby excluding the possibility of involvement of L-Au-OH species in the reaction. Such an acid effect was also noted in the recent report by Roithova et al [17] …”
Section: Resultssupporting
confidence: 81%
“…Maier and Zhdanko’s study suggested gem-diaurated species cannot directly undergo protodeauration, which is not directly involved in the catalytic cycle, whereas Roithova and co-worker’s results showed the alkyne could assist the dissociation of diaurated species, which was involved in the reaction cycle. [16,17] Houk, Vilhelmsen, and Hashmi computed that in some reactions the gem-diaurated species is in the catalytic cycle. [6g,h] Inspired by the previous work, we hypothesize that the bis-gold intermediate would be more difficult to form if the gold catalyst concentration is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, this study provides useful information that will enable future in silico studies of mechanism and structure/activity relationships. By DFT calculations it is shown that the dual gold mechanism is favoured, but this does not exclude the monogold catalyst, as stated recently, 47 especially if the catalyst loading is low. It will depend on the facility to join two metal moieties.…”
Section: Discussionmentioning
confidence: 78%
“…46,47 However, there is much ongoing debate about the relative competence of mono-and digold mechanisms for many gold-catalysed reactions. Even in situations where dual metal-catalysed mechanisms were not thought to be operative, there are some recent examples where calculations revealed cooperative effects; for example, there are examples of heterogeneous catalysis where changing the surface allowed adjacent sites to achieve cooperative catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[12] They are also very useful as catalysts for multicomponent reactions [13][14][15] and in the synthesis of heterocycles, [16] and are widely embedded in the concept of asymmetric catalysis. [30] Moreover, ESI-MS can be coupled to ion spectroscopy, [31][32][33][34][35][36] that can provide conclusive information about the structure of trapped ions in the gas phase. As far as we know, there are no reports concerning the identity of the lanthanide intermediates formed in a reaction medium.…”
Section: Introductionmentioning
confidence: 99%